Discovery of a new cavernicolous trechine genus and species from a deep pit in Anlong, southwestern Guizhou Province (Coleoptera: Carabidae: Trechinae) - Tian, Mingyi; Huang, Sunbin (Zootaxa, 2021)
Ckacus youcha n. gen. & n. sp. is described and illustrated based on a single male discovered in the deep area of Luoshui Dong, a vertical cave in Anlong Xian, southwestern most of Guizhou Province, Southwest China. This new genus seems related to Bathytrechus Uéno, 2005 from Leye Xian, northwestern most Guangxi by its elongate body which is wholly pubescent, the tridentate right mandible and the well-striated elytra with the 1st interval extremely narrowed at apical 1/3, but differs in several important characters. In addition, three individuals of the species Satotrechus rieae Uéno, 2006 were also collected from -340 m to -450 m in the same cave. This species was formerly only known from four caves in Anlong and Ceheng counties.